If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 13 + 5(x + -2) * 3 Reorder the terms: 13 = 13 + 5(-2 + x) * 3 Reorder the terms for easier multiplication: 13 = 13 + 5 * 3(-2 + x) Multiply 5 * 3 13 = 13 + 15(-2 + x) 13 = 13 + (-2 * 15 + x * 15) 13 = 13 + (-30 + 15x) Combine like terms: 13 + -30 = -17 13 = -17 + 15x Solving 13 = -17 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 13 + -15x = -17 + 15x + -15x Combine like terms: 15x + -15x = 0 13 + -15x = -17 + 0 13 + -15x = -17 Add '-13' to each side of the equation. 13 + -13 + -15x = -17 + -13 Combine like terms: 13 + -13 = 0 0 + -15x = -17 + -13 -15x = -17 + -13 Combine like terms: -17 + -13 = -30 -15x = -30 Divide each side by '-15'. x = 2 Simplifying x = 2
| 2/3(x+4)=0 | | 1+3p-4p=-4(-12p+9)+3(p-5) | | -5(-5b-3)=7b+12+12 | | 1/6-2/3m=1/4 | | 0=6.6x+4.9x^2 | | -3/4m-11/4m=-7/2 | | 1/3b-2=2 | | 400/150 | | x^4+2*x^3-2000=0 | | 8k-64= | | x^2+2x^2=81 | | 5q+3=2q+18 | | 4t+6=4t+10 | | 2x+55+45=400 | | 3n^2+40=23n | | 6x+3x-6x= | | 0.3x-0.4x+2=-3 | | 10n-8+n=20 | | -2v+2/3+3(2/3)=11(2/3) | | x/4-11=3x | | 4=1/3a | | 3j-3/8=3/4 | | 9(x+8)-7=65 | | 6y+15=5y+18 | | 35/56 | | 3=3/2x-3 | | 5/3x+5x=-35/3 | | 3x+8=5(1-x) | | 3x-36=51 | | (2x+40)=3x | | -b-2b-3b+4=-68 | | 0.4z=0.5(2z+6) |